Antioxidant activities of selected mango seeds / Kamarul Arifin Khalid - Khalid, Kamarul Arifin (Faculty of Applied Sciences, 2009)
This study was aimed to determine the total phenolic content and antioxidant activities in selected mango seeds. Three different types of mango {Mangifera indica L.) commonly available in Malaysian supermarkets namely, 'Chokanan', 'Maha' and 'Madu' were selected. Ethanol was used as a solvent because it is safe to be used in the food system. Phenolic content was determined using a Folin-Ciocalteu assay. Antioxidant activitites were determined using FRAP and DPPH assays. Based on analysis of variance, 'Madu' showed the highest amount of total phenolic content (3994.27 ± 20.6 mg GAE/g) and 'Chokanan' had the lowest total phenolic content (3424.33 ± 76.7 mg GAE/g). However, 'Chokanan' showed the highest ferric reducing power for FRAP assay, followed by 'Maha' and 'Madu' extract. For radical scavenging activity using 2,2 - diphenyl - 1 - picrylhdrazyl (DPPH) method, the highest effect of scavenging free radical showed by 'Madu' followed by 'Maha' and 'Chokanan' seed which were 95.08±0.052 %, 94.68±0.044 %, and 94.56±0.041 % respectively. All the mango seed extracts had lower antioxidant activity compared to BHA/BHT. Mango seeds will be a potential for natural antioxidants.